What Is the Optimal Adjuvant Treatment Sequence for Node-Positive Endometrial Cancer? Results of a National Cancer Database Analysis. Issue 2 (1st February 2018) - Modh, Ankit; Ghanem, Ahmed I.; Burmeister, Charlotte; Hanna, Rabbie K.; Elshaikh, Mohamed A.
Abstract : Objective: The optimal sequence of administering chemotherapy (CT) and radiation treatment (RT) in women with node-positive endometrial carcinoma (EC) remains controversial. We used the National Cancer Database to evaluate overall survival (OS) in women with advanced EC receiving different sequences of adjuvant therapy. Methods: The National Cancer Database was queried for female adults with International Federation of Gynecology and Obstetrics 2009 stage IIIC1 to IIIC2 EC diagnosed from 2004 to 2012 treated with hysterectomy and adjuvant CT and RT. Overall survival was compared between sequential treatment (CT followed by RT) and concurrent treatment (CT and RT within 4 weeks). χ 2 tests assessed differences by sequence and various clinical variables. Log-rank test and Cox proportional hazards models evaluated OS. Risk factors related to OS were identified by univariate and multivariate analyses. Results: Of 1826 patients, 67% (1218) received sequential treatment and 33% (608) received concurrent treatment. The median follow-up was 49.2 months. The sequential treatment group had a better 5-year OS (67% [95% confidence interval = 64%–70%]) than the concurrent treatment group (62% [95% confidence interval = 57%–66%]) ( P = 0.004). On multivariate analysis, the strongest predictors of worse OS were increasing age (hazard ratio [HR] = 1.04 [1.02–1.06], P = 0.0003), type 2 versus type 1 EC (HR = 1.60 [1.06–2.43], P = 0.03), grade 3 versus 1 (HR = 2.64 [1.23–5.67], P = 0.01), residual disease or positive margin versus negative margin (HR = 2.25 [1.43–3.56], P = 0.0005), and concurrent versus sequential treatment (HR = 1.67 [1.15–2.40], P = 0.006). Conclusions: This study suggests that upfront CT followed by RT may be a better treatment sequence for adjuvant therapy in women with advanced EC.